Preferensi Konsumen Sektor UMKM pada Bank Umum Syariah di Kota Ambon (Pembiayaan Modal Kerja & Investasi) - Afdhal Yaman; Arizal Hamizar; Muhammad Reza Nacikit; Dety Aryani Relubun; Fatmah Watty Pelupessy; Muammar W. Maruapey; Fadli Fendi Malawat; Rajab Rajab (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to understand the preferences of MSME consumers in Ambon City toward working capital and investment financing provided by Islamic Commercial Banks (BUS). Amid competition with conventional banks, BUS holds significant potential to offer financing aligned with Sharia values, though it has yet to become the primary choice for many business owners. This study identifies the factors influencing MSMEs' decisions to choose BUS, deemed relevant for the development of the MSME sector in Ambon City. The research method used is a qualitative approach involving in-depth interviews and participatory observation with MSME actors in Ambon City. Through thematic analysis, data is processed to explore perceptions, experiences, and factors influencing MSMEs' choice of Sharia financing. The results show that MSMEs' preference for BUS is driven by adherence to Sharia principles, the flexibility of profit-sharing schemes, and ease in requirements and application processes. The profit-sharing scheme implemented by BUS provides advantages in terms of flexible payments adjusted to business income, especially for businesses with fluctuating cash flows. Additionally, guidance from BUS in investment planning offers significant added value for MSMEs in long-term business development.